DECISION MAKING TO VISIT KOPI LUWAK AGROTOURISM (Case Study of Kopi Luwak Cikole in Cikole Village, Babakan Village, Lembang District) - Fadhila, Elma Dian; Deliana, Yosini (Institut Pariwisata dan Bisnis Internasional, 2019)
The agricultural sector in tourism is often called agrotourism. Kopi Luwak (Civet Coffee) Cikole, located in Kampung Babakan, produces Luwak coffee that applies animal welfare, so that agrotourism is awarded as Animal Wellfare-based agro-tourism. Kopi Luwak Cikole offers educational tours for its visitors. Visitorsto agrotourism are thought to have a specific purpose. Various people who visit Agro Tourism are seen from the characteristics of visitors and visiting decision making. The purpose of this study is to identify the characteristics and consumer decision-making processes of Kopi Luwak Cikole. Data analysis was carried out with descriptive analysis techniques. The results of this study indicate that the characteristics of Kopi Luwak Cikole respondents are mostly resident of Malaysia, male, 36-45 years old, their last education is Bachelor, have occupation as a Private or Government Employee with monthly income ≥ Rp. 5,000,001. The visiting decision at the need recognition stage is the motivation to visit agro tourism. This is because attractive facilities with benefits sought during a visit are adding to the knowledge of cultivation and process of civet coffee. Evaluation phase, consideration for visiting is because of civet coffee education. Furthermore, the decision to visit is carried out in a planned manner which on average is carried out during holidays. The level of satisfaction after post-visit, shows visitors feel satisfied with the facilities in agrotourism.